Editors' Note: Clinical, Neuroimmunologic, and CSF Investigations in First Episode Psychosis. (23rd November 2021) - Lewis, Ariane; Galetta, Steven
Abstract : In "Clinical, Neuroimmunologic, and CSF Investigations in First Episode Psychosis, " Guasp et al. and the Barcelona group reported that 21 of 105 patients with first-episode psychosis (FEP) met the criteria by Pollak et al. for possible or probable autoimmune psychosis (AP), none of whom had autoimmune antibodies or developed NMDAR encephalitis. In a separate cohort, 2 of 3 patients referred for a second opinion with FEP who had NMDA receptor antibodies did not meet the criteria by Pollak et al. for possible AP. They concluded that the criteria by Pollak et al. are overly dependent on neurologic features and propose their own algorithmic approach to screen for AP, which includes the performance of MRI, EEG, and testing for serum neuronal antibodies for all patients with FEP even in the absence of neurologic warning symptoms. Pollak et al. commented that all 3 patients in the one FEP cohort with autoimmune antibodies, in fact, met the criteria for possible AP because of the presence of a movement disorder and/or cognitive dysfunction. Furthermore, they questioned the recommendation by Guasp et al. to perform an extensive workup in the setting of FEP without neurologic symptoms because of concern that this is not only a poor use of resources but it is also not feasible in most psychiatric settings. Dalmau et al. and the Barcelona group respond that (1) although echolalia is one of the 12 features of catatonia, it can be present independently and (2) because there is a broad differential diagnosis for FEP, which includes systemic, neurologic, and psychiatric disorders, facilities that care for patients with FEP must be able to perform a thorough diagnostic evaluation themselves or transfer patients elsewhere.